2015
DOI: 10.3892/mmr.2015.4496
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol preserves neural function and attenuates the pathology of Alzheimer's disease in mice

Abstract: Alzheimer's disease (AD) is the most common form of dementia and there currently are no effective treatment strategies available. Catalpol is an iridoid glucoside, and large quantities can be isolated from the genus Rehmannia (Orobanchaceae). The present study assessed whether catalpol had any protective effects against Alzheimer's disease using a murine model. Reactive oxygen species (ROS)-associated enzymes as well as soluble Aβ40 and Aβ42 were detected using kits. Thioflavin‑S staining was performed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…For example, evidence implied that the anti-aging effects of catalpol, an iridoid glycoside from Rehmannia, were achieved by promoting endogenous antioxidant enzyme activities and normalizing energy disturbance (Huang et al. 2016 ). However, the effect of iridoids in P. decorate targeting in the treatment of oxidative stress related neurological diseases has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…For example, evidence implied that the anti-aging effects of catalpol, an iridoid glycoside from Rehmannia, were achieved by promoting endogenous antioxidant enzyme activities and normalizing energy disturbance (Huang et al. 2016 ). However, the effect of iridoids in P. decorate targeting in the treatment of oxidative stress related neurological diseases has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that catalpol plays a role in protecting primary cultured neurons against Aβ toxicity via inhibiting mitochondrion dysfunction and neuroinflammation (Jiang et al, 2008a ; Liang et al, 2009 ). Catalpol can reduce the oxidative stress, decrease the levels of soluble Aβ, and thus inhibit the plaque formation in a mouse model of AD (Huang et al, 2016 ). The present study, for the first time, has revealed the underlying mechanism of catalpol on inhibiting Aβ production: catalpol reduces Aβ generation through promoting α-cleavage of APP processing.…”
Section: Discussionmentioning
confidence: 99%
“…Advancements have been made in the use of natural products to prevent AD. Catalpol, one of the iridoid glycoside compounds extracted from Rehmannia glutinosa , has shown beneficial effects on neurodegenerative diseases, such as Parkinson’s disease (PD) and AD (Mao et al, 2007 ; Bi et al, 2008 ; Huang et al, 2016 ). Catapol has a wide range of biological activities, includinganti-oxidation, anti-inflammation, anti-aging, anti-tumor and anti-apoptosis properties (Pungitore et al, 2004 ; Bi et al, 2013 ; Chen C. et al, 2013 ; Chen W. et al, 2013 ; Wei et al, 2014 ; Yang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalpol can improve memory and reduce neurodegeneration by increasing BDNF expression [97]. In vitro, catalpol has been able to reduce the levels of soluble Aβ40 and Aβ42 in the cerebral cortex, and thus, inhibit the formation of senile plaques [98].…”
Section: Catalpolmentioning
confidence: 99%